Foreword - De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
It is a great honor for me to introduce this supplement of Acta Biomedica on " Growth and Nutritional Changes in Qatari Children after Medical and Nutritional Interventions". [...]